Resolution of Disputes on Disclosure of Public Information: Judicial Approach Through Adjudication and Litigation Based on the Law Number 14 of 2008 concerning Openness of Public Information - Siregar, Hisar; Nababan, Roida; Habeahan, Besty; Gulo, Belva Frederic (Golden Ratio of Law and Social Policy Review, 2025)
Public information disclosure has become a pressing legal issue due to its significance in ensuring transparency and its role as a pillar of a healthy democracy. It serves as a crucial tool for guaranteeing the public’s right to know what the government is doing, has done, and plans to do. Law No. 14/2008 on Public Information Disclosure aligns with fundamental principles in Indonesian Constitutional Law, including the right to communicate and access information as stated in Article 28F of the 1945 Constitution. This research aims to address two key questions: 1) What is the role of Law No. 14/2008 within the Indonesian constitutional system? and 2) How is the law implemented in resolving public information disputes, particularly in ensuring the equal distribution of Information Commission institutions across districts and cities in North Sumatra? The research uses a normative juridical approach and a qualitative method, focusing on a deep understanding of the issue rather than generalization. Ultimately, the study seeks to propose the establishment of District/City Information Commissions throughout North Sumatra, which would assist local communities in resolving public information disputes more efficiently, reducing the need to travel to the North Sumatra Information Commission in Medan and thereby saving time and costs for all parties involved.